An Outcome Evaluation of the Philippine Health Technology Assessment Program - John Q. Wong; Stephanie Anne L. Co; Cheyenne Ariana Erika Modina; Krizelle Cleo Fowler; Mary Gil Tarroc; Eunice U. Mallari; Abigail L Tan; Carlo Yao (Philippine Institute for Development Studies (PIDS), 2022)
The passage of the UHC law in 2019 mandated the creation of the Health Technology Assessment (HTA) Program to identify and recommend the most cost-effective health technologies for the Philippine government to procure. Since its inception, the HTA has mostly assessed COVID-19 related technologies. But with changing demands, current HTA processes must be evaluated for its relevance and usefulness post-pandemic, and performance relative to international best practices. More importantly, there is a need to assess far-reaching impacts of pricing and procurement on end-users themselves. Given these indices, this study reviewed HTA policies and assessed outcomes through end-user responses. Special attention was given to the utilization, assessment, and satisfaction with the processes, reports and recommendations of the HTA. The HTA roadmap has been delayed by multiple factors, including changes in leadership and the COVID-19 pandemic. However, end-users still utilize HTA assessments and recommendations in agenda-setting, policy-formulation, decision-making, and procurement. This was especially apparent for technologies related to COVID-19. But despite these achievements, much can be improved. HTA must navigate through the challenges of inadequate local data. It must also consider adopting international best practices and adding human resources to increase capacity for assessments and improve current processes. Finally, the program must transition to essential medicine and technologies for high-burden diseases and widen its scope, given its value to agencies involved in improving public health.
Keywords: 330; health technology assessment; HTA; outcome evaluation; Philippines